2018
DOI: 10.1016/j.cities.2018.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for housing attributes in Saudi Arabia: A comparison between consumers' and property practitioners' views

Abstract: Due to rapid urbanisation, population growth and limited supply of housing, the housing sector in Saudi Arabia is facing significant challenges. There have been attempts to provide largescale housing projects to combat this issue. However, there are concerns that short-term policies to provide large quantities of housing can result in low-quality units which are underside by consumers. Therefore, understanding consumer preferences with regard to housing is crucially important if housing projects are to be succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 71 publications
2
23
0
5
Order By: Relevance
“…Housing preferences research has been developing for decades. Some has examined the role of sociocultural and demographic characteristics in different societies on the individual preference criteria [ 38 , 39 ]. Hooimeijer [ 40 ] stated that household priorities change through changes in individual's life and housing marketing.…”
Section: Introductionmentioning
confidence: 99%
“…Housing preferences research has been developing for decades. Some has examined the role of sociocultural and demographic characteristics in different societies on the individual preference criteria [ 38 , 39 ]. Hooimeijer [ 40 ] stated that household priorities change through changes in individual's life and housing marketing.…”
Section: Introductionmentioning
confidence: 99%
“…Factor 6: Intrinsic factors Cupchik, Ritterfeld, and Levin ( 2003) in Mulliner and Algrnas (2018) described intrinsic attributes to include house size, interior layout, design, and functionality, space, number of rooms, and internal design (Mulliner and Algrnas 2018). Therefore, it was considered the sixth factor in this research due to its focus on space arrangement in occupancy.…”
Section: The Explanation Of Each Of the Factors Indicated In The Table Is As Followsmentioning
confidence: 99%
“…The attributes included in the extrinsic factors include the exterior design or building facades, quality of building materials, and the availability of green open space (Mulliner and Algrnas 2018). Therefore, extrinsic attributes were used as the seventh factor due to their focus on the arrangement of space outside the occupancy.…”
Section: Factor 7: Extrinsic Factorsmentioning
confidence: 99%
“…Based on previous study made by Mulliner and Algrnas [3] have shown in the perspective of Saudi Arabia residents the most important attributes that should be taken into consideration of developers are building quality and materials, neighborhood safety, cleanliness and quality, thermal comfort and exterior finishing. The study also finds out that housing attributes in perspective professional preferences.…”
Section: Affordable House Buyers' Preferencesmentioning
confidence: 99%